Whither the welfare state? The macroeconomics of social policy - Jamee K. Moudud; Ajit Zacharias (Levy Economics Institute of Bard College, 2000)
The idea that saving is the force driving private investment and economic growth has become ever more entrenched in mainstream economic thought as well as in the minds of policymakers and the general public. Even though the empirical evidence that increased household saving will directly stimulate private investment and economic growth is scant, the idea remains prominent and underlies policy debates on topics ranging from Social Security to a balanced federal budget to reducing the national debt. The popular theory underlying these cuts is countered by evidence that private sector investment is financed primarily out of business retained earnings, not household saving, which explains why current policies aimed at raising household saving via cuts to social spending programs have been unsuccessful at raising saving rates. Moreover, government spending on social programs does not necessarily reduce economic growth. Higher government spending could be supported, and a greater degree of investment spending stimulated, through a combination of lower taxes on business income and higher taxes on personal incomes of upper-income households.
Keywords: 330; Sozialstaat; Sozialpolitik; Öffentliche Sozialausgaben; USA; Makroökonomischer Einfluss